Different sink : Source relationships existing in rubber (Hevea brasiliensis) during different months in the North East Indian climatic conditions - Dey S K (2nd International Congress of plant physiology on sustainable plant productivity under changing environment 8-12 January, 2003, New Delhi)
The factors contributing towards low and high rubber yield during May and November in Hevea brasiliensis were studied by analyzing the sink strength of high yielding Hevea clones. Yield is generally low during summer months and high during winter months in this region. The major yield components like initial flow rate, dry rubber content and plugging index showed a wide difference in both the months/seasons. High temperature prevalent during May causes early plugging and stoppage of latex flow by way of reducing the total yield. However, low temperature during November prolongs the flow of latex due to delay in plugging favouring high yield. The stored carbohydrate pools of bark (tree trunk) and sugar in latex were high during May indicating inability to utilize the available resources. Reduction of storage and low sugar in latex and subsequent increase in photosynthetic rate duting November indicates higher utilization of photosynthates due to high sink demand. In general, the yield of rubber is limited more by sink capacity during May and source capacity during November in the North East Indian climatic scenario.
Keywords: Flow rate; Plugging index; Rubber content; Sink; Yield